Comparison of Office Lighting Alternatives in Terms of integrative Lighting - Kaplan, Elif Erkoc; Ozturk, Leyla Dokuzer (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2021)
It is well-known that light has biological and behavioural effects in addition to its visual effects. These effects are described as non-image-forming or non-visual responses. Lighting design considering the visual and non-visual effects of light is expressed in terms such as integrated lighting or human centric lighting. However, there is still no consensus on the illuminance and colour temperature to be provided depending on the type of task or activity in the sense of human centric lighting. The aim of this study is to determine the lighting conditions in an office that are biologically effective, meet the visual requirements and at the same time is rated as positive by the occupants. For this purpose, four static lighting scenarios and one dynamic lighting scenario are created in an office room, which differ in terms of illuminance and correlated colour temperature. These scenarios are compared with regard to visual and non-visual effects of light through surveys and alpha- opic equivalent daylight (D65) illuminance calculations. The composition of static scenarios are '500 lx, 4000 K', '1000 lx, 5500 K', '1250 lx, 4000 K', '1500 lx, 5500 K'. The limits of the dynamic scenario are '500 lx-1000 lx' and '3500 K-5500 K'. These values are provided on the task area of the worktable chosen as a reference to adjust the scenarios through the lighting control system. In order to determine the biological potential of light quantitatively, the melanopic equivalent daylight illuminance was calculated for each working table in the office room. The spectral irradiance data measured at eye level were used in this calculation. In addition to the questions about the determination of the emotional states of the participants, questions about the evaluation of the lighting scenario with regard to illuminance, colour temperature of light, influence on the working conditions and ambient atmosphere were also included in the questionnaire. The statistical evaluation of the survey data was carried out for two different conditions, a long-term and a short-term study. Academic staff working in the mock-up room participated in the long-term study, in which each scenario was implemented for 2 weeks. The participants of the short-term study, in which each scenario was applied for 20 minutes, were academicians, doctoral and master's students. It became apparent that high illuminance and/or cool colour of light are effective in feeling alert, rested and energetic. However, the preference of the participants was generally in favour of the neutral light colour. Regarding illuminance 500 lx was evaluated as low and 1500 lx as high. The scenario that was found to be the most positive in terms of the illuminance, the colour temperature of light and its effect on the working conditions in both long- and short-term study was '1250 lx, 4000 K'. The appreciation of the neutral light colour can also play a role in this result. It was found that the variable ambient atmosphere in dynamic lighting is more natural than static scenarios with 500 lx and 1000 lx. Preferences may conflict with each other in terms of visual and non-visual effects of light. Instead of continuously using scenarios with high illuminance and/or cool light colour, the implementation in shorter periods of time, in which people have to feel more alive and alert, can be a rational and balanced solution. The results of this study, in which the visual and non-visual effects of lighting scenarios with different illuminances and colour temperatures on office workers are assessed, can be considered to determine the optimal conditions for integrated lighting in offices.
Keywords: Colour temperature; dynamic lighting; human centric lighting; illuminance; static lighting; GANGLION-CELLS; PERFORMANCE; ALERTNESS; SLEEP; MOOD; Architecture